Unlocking Fluent Speech: Enhancing Student Speaking Skills through Digital Storytelling - Nurhikmah, Zizi (English Education Department at FKIP Nommensen University, 2024)
This study evaluates the impact of digital storytelling on improving college students' speaking skills, based on Vygotsky’s Social Constructivism, which emphasizes the role of social interaction and cultural tools in learning. Using a quasi-experimental design, 60 fourth-semester students at the Islamic Institute of Sunan Kalijogo Malang were divided into an experimental group and a control group. The experimental group from the Faculty of Islamic Da'wah and Broadcasting engaged in digital storytelling, while the control group, including students from the Tarbiyah and Teaching Faculty, did not. Narrative texts such as fairy tales and fables were used in the intervention. The experimental group showed a significant improvement in speaking skills, with their mean post-test score increasing from 55.39 to 61.72, compared to a decrease in the control group's score from 57.01 to 55.12. Digital storytelling effectively enhances students' speaking skills by providing engaging, interactive learning experiences. The study supports the integration of digital storytelling into language instruction to improve oral communication abilities